Unmanned Aerial Vehicles 2010
DOI: 10.1007/978-94-007-1110-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Take Off, Tracking and Landing of a Miniature UAV on a Moving Carrier Vehicle

Abstract: We present a system consisting of a miniature unmanned aerial vehicle (UAV) and a small carrier vehicle, in which the UAV is capable of autonomously starting from the moving ground vehicle, tracking it at a constant distance and landing on a platform on the carrier in motion.Our visual tracking approach differs from other methods by using low-cost, lightweight commodity consumer hardware. As main sensor we use a Wii remote infrared (IR) camera, which allows robust tracking of a pattern of IR lights in conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 18 publications
0
62
0
1
Order By: Relevance
“…It has been shown that the PixArt IR tracking sensor can be successfully applied in a visual servoing algorithm on a quadrotor vehicle [3], without the need for powerful processing hardware. The position and yaw angle are estimated from visual information, while the pitch and roll angles are obtained from the IMU.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the PixArt IR tracking sensor can be successfully applied in a visual servoing algorithm on a quadrotor vehicle [3], without the need for powerful processing hardware. The position and yaw angle are estimated from visual information, while the pitch and roll angles are obtained from the IMU.…”
Section: Related Workmentioning
confidence: 99%
“…In this work measurements using an on-board PixArt infrared (IR) tracking sensor are used with a point-based pose estimation algorithm [5] to compute the full 6 DOF pose in real-time for visual servoing purposes. Although the PixArt IR tracking sensor has been used in visual servoing of MAVs before [3], it has not previously been implemented using a general pose estimation algorithm. The small size, low weight and cost of the IR tracking sensor allow for implementation on a low-cost MAV platform and detection of active IR markers allows for robust performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drift in position and yaw is either very low or even eliminated by using known, world-fix structures. Sensors that are commonly used for map generation are laser scanners [6], [7] or cameras incorporating known markers [8], [9] or SLAM/VO techniques [10], [11]. Since laser scanners are still too heavy and power hungry for small quadrotor systems, our work focuses on vision based approaches.…”
Section: A Control and Navigation Based On Mapsmentioning
confidence: 99%